A revisit to the regions of some van den Bergh open clusters using photometric and astrometric parameters - Orellana, Rosa Beatriz (2014)
We present results of a study that combines photometry and astrometry for the open clusters vdB80, vdB85 and vdB130. We apply a model which analyses the proper motion distribution and the stellar density to find the kinematic parameters and stellar membership in the region of the mentioned open clusters. The astrometric data are obtained from UCAC4 catalogue. For each cluster, we report the centre coordinates, the components of mean proper motion, the angular diameter and the astrometric members. They are: vdB80: α=97°.73938±0°.00846,δ=-9°.66953±0°.01177,μαcosδ=-2.13±0.47mas/yr,μδ=-0.95±0.47mas/yr,12′, 15 members; vdB85: α=101°.71670±0°.00808,δ=1°.34392±0°.01253,μαcosδ=0.89±0.43mas/yr,μδ=3.24±0.43mas/yr,8′, 9 members; vdB130: α=304°.44001±0°.01407,δ=39°.32745±0°.00726,μαcosδ=-4.14±0.25mas/yr,μδ=-5.15±0.25mas/yr,9′, 9 members. We analyse the incidence of the proper motion errors in the determination of the cluster parameters and of the stellar membership and find that they are not significantly changed. We finally compare the astrometric members with the photometric ones given in the literature.